Writing Canadian Judaism through Queer Migration - Gleibman, Shlomo (Canadian Jewish Studies / Études juives canadiennes, 2026)
This essay places the literary representations of Canadian queer Jews from the former Soviet Union, such as in David Bezmozgis’s short story “Minyan,” in a larger context of Canadian queer Jewish writing that addresses the themes of immigration or migration, such as Brian Stein’s short story “The Good Son” and K. David Brody’s novel Mourning and Celebration. This article thus discusses three works where immigration/migration reflects a recouping of traditional symbols of Jewish life in the contexts of Canadian Judaism, Jewish community, and gay male sexuality. The article pursues answers to the following questions: How does the experience of immigration to Canada or migration within Canada influence one’s sense of cultural loss and strategies of reclamation? How are these representations of queer Jewish life shaped by and contribute to the diversity and multiculturalism of Canadian society?